A case of resected primary pulmonary pleomorphic carcinoma with long-term survival after multidisciplinary treatment - Iijima, Yoshihito (Surg Case Rep, 2020)
BACKGROUND: Generally, primary pulmonary pleomorphic carcinoma is resistant to treatment and has a poor prognosis. We report a case of resected primary pulmonary pleomorphic carcinoma with long-term survival after multidisciplinary treatment. CASE PRESENTATION: A 74-year-old man with a history of emphysema, pneumoconiosis, and chronic bronchitis presented with left lung nodule and left adrenal tumor based on computed tomography. We suspected clinical T1bN0M1b, stage IVB lung cancer. Adrenalectomy of the left adrenal tumor yielded a definitive diagnosis of pleomorphic carcinoma. Chemotherapy was performed despite the spontaneous regression of lung lesions. Since lung lesions re-enlarged 11 months after adrenalectomy, the left lower lobe was partially resected followed by chemotherapy. The lung lesion was the primary lesion of the adrenal tumor. There was no recurrence 100 months after the lung resection. CONCLUSIONS: The patient experienced long-term survival after multidisciplinary treatment. Both multidisciplinary treatment and immunological mechanisms caused spontaneous regression of the primary lesion.